Desarrollo de un método para tratamiento de aguas residuales como resultado de la integración de tres métodos biotecnológicos - Rodríguez Montenegro, Lisney (Ingenierias, 2017)
The purpose of this paper is to define and analyze three types of biotechnological treatments as a solution to this problem and how to create a better alternative in the treatment of urban wastewater from the integration of those cases. The cases studied are methods involving the use of microorganisms for conditioning Urban Wastewater (UWW), the first study case is the use of aquatic plants for the treatment of the UWW, that is a technology that allows to improve the quality wastewater mitigating the environmental impact, through the creation of wetlands, which at the same time become functional systems that generate and maintain life, and likewise in the second study case where is obtained through heavy metals bio-sorption via biomass is possible to obtain water that can be discharged into water bodies without generating big impact and with a lower degree of toxicity on the other hand the biological nitrogen removal method of treatment allows for the optimization of UWW conditions without causing environmental impact through nitrification and denitrification of the effluent with the use of microorganisms